EDUCATORS SHOULD BE PREPARED FOR SUSTAINABLE DEVELOPMENT AND GLOBAL CITIZENSHIP - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 25 January 2017 Teachers should be prepared for sustainable development and global citizenship based on the 17 global new agreements on the new Sustainable Development Goals (SDGs).